Dynamics and synchronization of the Hastings-Powell model of the food chain - Lonngren, KE; Bai, EW; Uçar, A (Pergamon-Elsevier Science Ltd, 2004)
The dynamic behavior of the nonlinear model suggested by Hastings and Powell to describe a three species food chain has been investigated. The synchronization of two models with different set of parameters has been achieved by using techniques from modern control theory. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Active Control; Systems; Rossler